Big words, small farmers:: Exploring academic overflows and ‘surplus water’ in Motupe, Peru - Domínguez Guzmán, Carolina (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
In the Motupe valley on the north coast of Peru, the cultivation of mango for export is in the hands of smallholders, many of whom cultivate on communal lands without water rights or official approval to grow perennial crops. In this article I present the case of the smallholders, known as excedentes de agua, who only have access to irrigate in time of abundance or excess water. Although these small farmers are considered displaced by modern agro-export, they and their mango plantations have managed to put down roots in a desert climate and adverse market sector. They challenge in this way, not only such conditions for doing agriculture, but also how to write about them and their water realities. It is this last point that constitutes the main contribution of this work. Inspired by actor-network theory, this article presents alternative ways to situate the partial ontologies that emerge from the case study as a point of interference – to converse or interchange with the grand narratives and their holistic aspirations, without having to add to them.